Studies on human plasma C1 inactivator-enzyme interactions. I. Mechanisms of interaction with C1s, plasmin, and trypsin. - Harpel, P C (J Clin Invest, 1975)
This study has explored the nature of the molecular events which occur when C1 inactivator, a human plasma inhibitor of the complement, kinin-forming, coagulation, and fibrinolytic enzyme systems, interacts with C1s, plasmin, and trypsin. Purified inhibitor preparations demonstrated two bands, when examined by acrylamide gel electrophoresis in the presence of sodium dodecyl sulfate (SDS). The molecular weights of the major and minor bands were 105,000 and 96,000 daltons, respectively. The minor component appeared to be immunologically and functionally identical to the main C1 inactivator component. Loss of C1s and plasmin functional activity was associated with the formation of a 1:1 molar complex between the inhibitor and each enzyme. These complexes were stable in the presence of SDS and urea. The light chain of both these enzymes provided the binding site for C1 inactivator. Complex formation and enzyme inhibition occurred only with native and not with an inhibitor preparation denatured by acid treatment, thereby demonstrating the importance of conformational factors in the enzyme-inhibitor reaction. Although peptide bond cleavage of the C1 inactivator molecule by C1s was not documented, plasmin was found to degrade the inhibitor with the production of several characteristic derivatives. At least one of these products retained the ability to complex with C1s and plasmin. Trypsin, which failed to form a complex with C1 inactivator, degraded the inhibitor in a limited and sequential manner with the production of nonfunctional derivatives one of which appeared structurally similar to a plasmin-induced product. These studies therefore, provide new information concerning the molecular interactions between C1 inactivator and several of the proteases which it inhibits. IMAGES: